2012
DOI: 10.1105/tpc.112.098905
|View full text |Cite
|
Sign up to set email alerts
|

A PP6-Type Phosphatase Holoenzyme Directly Regulates PIN Phosphorylation and Auxin Efflux in Arabidopsis

Abstract: The directional transport of the phytohormone auxin depends on the phosphorylation status and polar localization of PIN-FORMED (PIN) auxin efflux proteins. While PINIOD (PID) kinase is directly involved in the phosphorylation of PIN proteins, the phosphatase holoenzyme complexes that dephosphorylate PIN proteins remain elusive. Here, we demonstrate that mutations simultaneously disrupting the function of Arabidopsis thaliana FyPP1 (for Phytochrome-associated serine/threonine protein phosphatase1) and FyPP3, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(140 citation statements)
references
References 71 publications
(117 reference statements)
2
137
0
1
Order By: Relevance
“…Our data suggest a model in which subcellular PIN3 localization shifts from basal to apical membranes in vascular cells near the wound to redirect auxin flow backward and thus maintaining high auxin levels in the proximal petiole vasculature. Interestingly, an auxin-dependent switch in PIN3 polarization contributing to auxin-flow reversal is involved in the shoot gravitropic response (Rakusová et al, 2016), where basal-to-apical shift in PIN localization has been described to depend on phosphorylation (Dai et al, 2012). It is thus tempting to speculate that auxin-dependent phosphorylation of PIN3 would be involved in maintaining high auxin levels in the petiole base vasculature during root regeneration.…”
Section: Vasculature Proliferation and Endogenous Callus Formationmentioning
confidence: 99%
“…Our data suggest a model in which subcellular PIN3 localization shifts from basal to apical membranes in vascular cells near the wound to redirect auxin flow backward and thus maintaining high auxin levels in the proximal petiole vasculature. Interestingly, an auxin-dependent switch in PIN3 polarization contributing to auxin-flow reversal is involved in the shoot gravitropic response (Rakusová et al, 2016), where basal-to-apical shift in PIN localization has been described to depend on phosphorylation (Dai et al, 2012). It is thus tempting to speculate that auxin-dependent phosphorylation of PIN3 would be involved in maintaining high auxin levels in the petiole base vasculature during root regeneration.…”
Section: Vasculature Proliferation and Endogenous Callus Formationmentioning
confidence: 99%
“…Together with in vitro evidence for PID-mediated phosphorylation of bacterially expressed PIN fragments and PID-dependent PIN phosphorylation in transient protoplast expression assays (Michniewicz et al, 2007), this led to models suggesting that PINs represent substrates for PID, although we are still lacking conclusive in planta evidence for a direct interaction. PID activity appears to be antagonized by a PP6-type phosphatase heterotrimeric protein complex, consisting of PHYTOCHROME-ASSOCIATED SERINE/THREONINE PROTEIN PHOSPHATASE (FyPP), SAPS DOMAIN-LIKE (SAL) and the PP2AA regulatory subunit, which was shown to interact with PIN proteins and to antagonize their phosphorylation (Michniewicz et al, 2007;Dai et al, 2012). Intriguingly, PP2AA phosphatase regulatory subunits were shown to colocalize with PIN proteins at plasma membrane domains (Michniewicz et al, 2007), consistent with a scenario in which modulation of phosphatase activity at the plasma membrane directly feeds back on PIN phosphorylation status, thereby shaping PIN sorting decisions (Fig.…”
Section: Protein Recycling and Phosphorylation As Mediators Of Membramentioning
confidence: 99%
“…In a recent study, we showed that Arabidopsis FyPP1 (for Phytochrome-associated serine/threonine protein phosphatase1) and FyPP3, two homologous catalytic subunits of PP6, physically interact with SAL (for SAPS-domain like protein) and PP2AA proteins (RCN1/PP2AA1, PP2AA2, and PP2AA3) to form a PP6-type heterotrimeric holoenzyme that directly regulates the phosphorylation status of PIN-FORMED (PIN) proteins (auxin efflux carriers) and subsequently affects auxin efflux and plant development (Dai et al, 2012a(Dai et al, , 2012b. In this study, we extend these findings by showing that FyPP also plays a critical role in regulating ABA signaling in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…The PP2A holoenzyme consists of an enzymatically active catalytic subunit (PP2Ac), a 65-kD regulatory A subunit (PP2A A), and a variable regulatory B subunit (PP2AB) (Farkas et al, 2007). Although there are high sequence similarities among the C subunits of PP6 and PP2A phosphatases, they were classified as different phosphatases because PP6 requires Zn 2+ for its activity, whereas PP2A does not require any cation Wang et al, 2007;Dai et al, 2012a). PPPs are ubiquitous enzymes in all eukaryotes, but their regulatory functions are largely unknown in plants (Farkas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%